Functioning of the Joint Commission of the representatives of the Conference of the Episcopate of Poland and the government of the Polish People Republic in 1980 - Stępień, Marek (Prawo Kanoniczne, 2023)
After the Second World War communists took over the power in Poland. The main purpose of the ruling party was introducing the principles of Marxist philosophy. In the center of ideological fight was the Roman Catholic Church perceived as serious obstacle or even threat in achieving their goals. In 1980 the Polish authorities again declared their will to normalize relations and to reactivate the Joint Commission of the Government and the Episcopate. After the resumption of the session, the work proceeded constructively. The communists as the rulers counted on the help of the Church in calming social moods and normalizing the situation after the unrest and strikes that took place at that time.